Relationship Between Housing Credits Offered by Banks, Housing Sales, and Unemployment in the Turkish Economy (2010:Q1–2020:Q3) - Haydar Karadağ (Sosyal Siyaset Konferansları Dergisi)
The uncertainty of the amount of money individuals would receive in the future increases when unemployment increases. This may decrease individuals’ housing demands. While housing credits given by banks to individuals that want to purchase houses increase housing demands, the increase in unemployment decreases the demand for housing credits, which in turn decreases housing sales. In this study, we investigated the relationship between housing credits offered by banks, unemployment, and housing sales in the Turkish economy using quarterly data comprising 2010:Q1–2020:Q3. In this context, the stationarity of the series was tested using the ADF (Augmented Dickey Fuller) unit-root test, and the series became stationary. Thereafter, we performed cointegration and causality analyses. The canonical cointegration regression test predictor was used for the coefficient prediction belonging to variables. The results show that a 1% increase in house credits increases unemployment by 0%, 46 units, and 1% increase in total house sales increases unemployment by 0%, 59 units. Furthermore, 1% increase in unemployment increases house credits by 1%, 67 units, and total house sales by 1%, 19 units.